Differentiation of Leukocytes of Dumbo Catfish (Clarias gariepinus) Infected with Aeromonas hydrophila and Treated with Bay Leaf Solution (Syzygium polyantha) - Tomuso Angdi Suryani Sinaga; Morina Riauwaty; Henni Syawal (Jurnal Akuakultur SEBATIN, 2023)
The research was conducted from January to October 2021 at the Laboratory of Fish Parasites and Diseases, Departement of Aquaculture, Faculty of Fisheries and Marine, University of Riau. The purpose of this research was to analyze and obtain the best dose of bay leaf solution to treat catfish (Clarias gariepinus) infected with Aeromonas hydrophilla. Bay leaf is a plant that has antibacterial properties in fish because it contains secondary metabolites, namely tannins, saponins, steroids, alkaloids, flavonoids, and essential oils. The method used is an experimental method with a Completely Randomized Design (CRD), one factor with five treatments. The treatment applied is Kn (without immersed with bay leaf solution and not infected by A. hydrophila), Kp (without immersed with bay leaf solution and infected by A. hydrophila), P1 (1000 ppm), P2 (1100 ppm), P3 (1200 ppm). The curing is done by immersed with bay leaf solution for 5 minutes, carried out three times with an interval of 24 hours and then maintained for 14 days after treatment. The result shown that bay leaf solution able to cure catfish infected by A. hydrophila. The best dose was 1200 ppm with average total leukocytes of 12.61 × 104 cells /mm3, leukocyte differentiation (lymphocytes 84.66%, Neutrophils 6.66%, Monocytes 8.66%), phagocytitosis activity is 35.33%, and the survival rate 96.67%.